Influence of Tube Current Settings on Diagnostic Detection of Root Fractures Using Cone-beam Computed Tomography: An In Vitro Study - Tangari-Meira, Ricardo [UNESP]; Vancetto, José Ricardo [UNESP]; Dovigo, Lívia Nordi [UNESP]; Tosoni, Guilherme Monteiro [UNESP] (Elsevier, 2017)
Introduction This study assessed the influence of tube current settings (milliamperes [mA]) on the diagnostic detection of root fractures (RFs) using cone-beam computed tomographic (CBCT) imaging. Method Sixty-eight human anterior and posterior teeth were submitted to root canal preparation, and 34 root canals were filled. The teeth were divided into 2 groups: the control group and the fractured group. RFs were induced using a universal mechanical testing machine; afterward, the teeth were placed in a phantom. Images were acquired using a Scanora 3DX unit (Soredex, Tuusula, Finland) with 5 different mA settings: 4.0, 5.0, 6.3, 8.0, and 10.0. Two examiners (E1 and E2) classified the images according to a 5-point confidence scale. Intra- and interexaminer reproducibility was assessed using the kappa statistic; diagnostic performance was assessed using the area under the receiver operating characteristic curve (AUROC). Results Intra- and interexaminer reproducibility showed substantial (κE1 = 0.791 and κE2 = 0.695) and moderate (κE1 × E2 = 0.545) agreement, respectively. AUROC was significantly higher (P ≤ .0389) at 8.0 and 10.0 mA and showed no statistical difference between the 2 tube current settings. Conclusions Tube current has a significant influence on the diagnostic detection of RFs in CBCT images. Despite the acceptable diagnosis of RFs using 4.0 and 5.0 mA, those settings had lower discrimination abilities when compared with settings of 8.0 and 10.0 mA.
Keywords: Cone-beam computed tomographic imaging; diagnostic imaging; root fractures; tube current